Cu-SiO2 hybrid bonding simulation including surface roughness and viscoplastic material modeling: A critical comparison of 2D and 3D modeling approach. (July 2018) - Wlanis, Thomas; Hammer, René; Ecker, Werner; Lhostis, Sandrine; Sart, Clément; Gallois-Garreignot, Sébastien; Rebhan, Bernhard; Maier, Günther A.
Abstract: Cu-SiO2 direct hybrid bonding is considered as one of the key enabling technologies for 3D integration. Previous studies showed that the main process parameters influencing the bonding quality are temperature and annealing time, as well as the mechanical stress at the Cu-Cu interface. The latter is influenced by thermo-mechanical stress introduced by the coefficient of thermal expansion mismatch of SiO2 and Cu and by geometrical effects. The modeling approach of the present study aims to shed light on the influence of surface roughness on the contact area formation between Cu pads. Roughness profiles measured with atomic-force microscopy are directly used as input for the simulation. This introduces considerable computational effort when explicitly modeled within finite element simulation. A sub-modeling technique is used to reduce the numerical cost. The common 2D modeling approach is critically compared to full 3D modeling of the surface topography. The dominant micro-mechanical temperature dependent deformation mechanisms are taken into account by continuum mechanics material models from literature. Accordingly, the stress driven instantaneous dislocation glide and the diffusion triggered climb assisted dislocation glide are taken into account by corresponding plasticity and creep material models. Highlights: Simulation study of roughness influence on direct copper bonding. Roughness profile AFM measured and explicitly modeled in FEM. Microscopic material behaviour modeled by homogenized material models. Instantaneous strain from dislocation motion modeled by plasticity model. Dislocation climb and diffusion mediated deformation modeled by creep law.